Significance and determinants of tobacco use: A brief review - Fatma Mojtaba Alsaid Ahmed; Syed Wali Peeran (Wolters Kluwer Medknow Publications, 2016)
Tobacco is a plant product derived from a variety of plants belonging to the genus Nicotiana. The alkaloid nicotine present in the plant leafs is a stimulant and has an addictive effect. The tobacco plants have been historically grown and used for recreational purposes by the American local population. The dried tobacco leaves are consumed as chewing tobacco, snuff, and smoked in a variety of dispensations. Tobacco use (TU) has an adverse effect on various body systems and is a determinant for different diseases ranging from cancers to atherosclerosis. TU is a modifiable environmental risk factor for various diseases. Hence, with public health education and behavior modification, its burden can be reduced in a given society. Thus, the understanding of the incidence and prevalence of its use is necessary. This review attempts to sum up the significance and determinants of TU.